Extractable nuclear antigen effect on the DNA anti-DNA reaction and NZB/NZW mouse nephritis. - Morris, A D (1975)
Extractable nuclear antigen (ENA) is composed of at least two components, one a ribonucleo-protein sensitive to ribonuclease or heat and the other a protein. Antibodies to ENA are associated with a relatively benign clinical course in patients with systemic lupus erythematosus (SLE) in which DNA anti DNA complexes are thought pathogenic. The effect of ENA and anti-ENA on DNA anti-DNA reactions in vitro was studied. ENA effectively inhibited an anti-DNA hemagglutination reaction but no effect was found on binding of radioactive DNA or on the anti-hemocyanin hemagglutination reaction. The inhibitory effect was not abolished by yeast ribonuclease (RNase), heating, or DNase. Anti-ENA HAD NO EFFECT ON ANTI-DNA hemagglutination. In vivo, ENA altered the NZB/NZW mouse nephritis thought to be a model for human SLE nephritis. These results suggest the possiblity of a role for ENA in alteration of diseases due to pathogenic DNA anti-DNA complexes.